IMPLEMENTASI METODE AGILE PADA APLIKASI PENGOLAHAN PENDAFTARAN SANTRI BARU UNTUK MENINGKATKAN EFISIENSI: Registration Application, Financial Information, Agile Method, Islamic Boarding School, Efficiency - Sari, Siti Fadilah; Feizal, Muhammad (JURNAL AKADEMIKA, 2025)
The development of information technology has encouraged Islamic boarding schools (pesantren) to shift from manual administrative systems to web-based systems. Until now, the registration of new students and financial record-keeping at the pesantren have often faced obstacles because they were still carried out manually, making them prone to delays, document accumulation, and data entry errors.This study develops a web-based registration and financial management application using the Agile method, with Laravel, MySQL, and black box testing. The application provides features for online new student registration, financial information management, and pesantren promotional media.The research results show that the application is capable of accelerating the registration process, reducing data errors, improving financial management efficiency, and strengthening transparency and public trust in the pesantren